From Fear to Fun: Exploring the Experience of Edutainment-Based Arabic Language Learning at Islamic Universities - Khusnul Himmah; Ahmad Maghfurin; Tuti Qurrotul Aini; Nasikhin Nasikhin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to explore students' views on the integration of edutainment in Arabic language learning at Islamic colleges, specifically at UIN Walisongo Semarang. Using a qualitative approach, this study collected data through in-depth interviews, questionnaires, and observations, and applied triangulation to ensure the validity of the findings. Data analysis followed the Miles and Huberman model—covering reduction, presentation, and conclusion drawing—to obtain a systematic understanding of student perceptions. Findings indicate that edutainment is implemented through three main strategies: interactive digital media, Islamic-context role-play, and the integration of arts such as songs and calligraphy. This approach successfully increased students' interest, confidence, and affection for Arabic, while reducing learning anxiety and creating an inclusive and enjoyable classroom atmosphere. The majority of students responded positively because this method was considered to facilitate understanding and reduce boredom, although some provided critical feedback to ensure that academic aspects were maintained, while a minority were sceptical about its effectiveness in mastering advanced grammar. The main challenges include resistance to a learning style that is considered too relaxed and technical constraints in the use of digital applications. The success of edutainment, therefore, depends heavily on balanced learning design, lecturer responsiveness, and adequate technological infrastructure support.